1993
DOI: 10.1126/science.8502996
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Phenotype Evolution of HIV-1 to Envelope V2 Configuration

Abstract: Biological variability of human immunodeficiency virus type-1 (HIV-1) is involved in the pathogenesis of acquired immunodeficiency syndrome (AIDS). Syncytium-inducing (SI) HIV-1 variants emerge in 50 percent of infected individuals during infection, preceding accelerated CD4+ T cell loss and rapid progression to AIDS. The V1 to V2 and V3 region of the viral envelope glycoprotein gp120 contained the major determinants of SI capacity. The configuration of a hypervariable locus in the V2 domain appeared to be pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
157
3
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(172 citation statements)
references
References 20 publications
11
157
3
1
Order By: Relevance
“…Although CCR-5 vs. CXCR-4 tropism is regulated largely by the envelope V3 loop, there has been a number of reports documenting the ability of the V1͞V2 region to modulate HIV-1 cell tropism and replication potential (30)(31)(32)(33), although others have suggested only a minor role for the V1͞V2 domain (34). Our data documenting a major role for V1͞V2 in regulating the interaction with CCR-3 support these previous findings and suggest that V1͞V2 is indeed likely to play a significant role in modulating the envelope:coreceptor interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Although CCR-5 vs. CXCR-4 tropism is regulated largely by the envelope V3 loop, there has been a number of reports documenting the ability of the V1͞V2 region to modulate HIV-1 cell tropism and replication potential (30)(31)(32)(33), although others have suggested only a minor role for the V1͞V2 domain (34). Our data documenting a major role for V1͞V2 in regulating the interaction with CCR-3 support these previous findings and suggest that V1͞V2 is indeed likely to play a significant role in modulating the envelope:coreceptor interaction.…”
Section: Discussionmentioning
confidence: 99%
“…5). Before virus isolates obtained positively charged amino acid residues in V3 that are typical for SI isolates, amino acid substitutions and insertions occurred in V2, resulting in elongated, more positively charged V2 domains with frequent addition or relocation of potential N-linked glycosylation sites [93]. More detailed analysis revealed that this V2 polymorphism may occur in only a minor fraction of the HIV-1 isolates present in an infected individual [99].…”
Section: Phenotype Evolution Of Hiv-1mentioning
confidence: 99%
“…4). In about 70% of primary SI but in only 35% of NSI HIV-1 isolates, the V2 domain is elongated and contains positively charged amino acid residues and extra or dislocated potential N-linked glycosylation sites [93,99]. Although statistical analysis and construction of chimeric proviruses suggested that these characteristics of V2 contribute to SI capacity, site-directed mutagenesis is required to formally prove this.…”
Section: Si Capacitymentioning
confidence: 99%
See 2 more Smart Citations